2015
DOI: 10.1016/j.jcrs.2014.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SRK/T and Haigis formulas for predicting corneal astigmatism correction with toric intraocular lenses

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…On the other hand, the difference in corneal plane effective cylinder power of toric IOLs between the method using a fixed ratio of 1.46 and that using ELP tended to be larger in eyes with small or large ELP [ 11 , 17 ]. A previous study demonstrated that the Haigis formula is more accurate than the SRK/T formula in predicting both refractive outcome and corneal astigmatism correction by toric IOLs [ 3 ]. The more accurate predictions of refractive outcome lead to better predictions of corneal astigmatism correction by toric IOLs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the difference in corneal plane effective cylinder power of toric IOLs between the method using a fixed ratio of 1.46 and that using ELP tended to be larger in eyes with small or large ELP [ 11 , 17 ]. A previous study demonstrated that the Haigis formula is more accurate than the SRK/T formula in predicting both refractive outcome and corneal astigmatism correction by toric IOLs [ 3 ]. The more accurate predictions of refractive outcome lead to better predictions of corneal astigmatism correction by toric IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study comparing the accuracy of the SRK/T and Haigis formulas for predicting corneal astigmatism correction with a toric IOL showed that the difference in the median absolute magnitude of error between the two formulas was significant but small [ 3 ]. In the IOL power calculation, modern IOL power calculation formulas provide similarly accurate estimates of refractive outcomes in an eye with an average AL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In der präoperativen Analyse zeigte sich die Haigis-Formel genauer als die SRK/T-Formel hinsichtlich Vorhersagbarkeit des refraktiven Outcomes und der effektiven Korrektur des topographischen Astigmatismus [43]. Es konnte gezeigt werden, dass die Clear-Cornea-Inzision an der steilen Achse zu einer signifikanten Reduktion der notwendigen zylindrischen Stärke der tIOL sowie zu einem geringeren Risiko eines postoperativen irregulären Astigmatismus führt [44].…”
Section: Vektorplanung Kann Unter Mitberücksichtigung Topographischerunclassified
“…11 The back-calculated effective lens position was defined as the postoperatively calculated effective lens position based on preoperative K, AL, implanted IOL power, and postoperative refraction. 1,11,12 The Haigis constant optimization Excel spreadsheet (Microsoft, Inc., Redmond, WA, USA) was used to calculate the data-adjusted SRK/T A-constant. 13 Refractive Prediction Error.…”
Section: Main Outcome Measuresmentioning
confidence: 99%